Back to the same place of holidays: An analysis of European tourists’ preferences towards cultural tourism - Amaral, Rui (2018)
Cultural tourism remains one of European tourists’ main preference for travelling inside Europe (Kozak, 2002; Chaldler & Costello, 2012). Travel has long been as-sociated with cultural standards and levels, because a visitor who is motivated to explore, discover and learn about the attractions of a country or region exert an incalculable personal, social and professional investment. Although several studies have been conducted revisit intentions to sun and sand destinations (among oth-ers, Correia & Zins, 2015). Thus, limited focus has been given to investigating re-turn reasons based on cultural tourism preferences (Kastenholz et al, 2013). This study aims to identify the preferences of Europeans in their demand for cul-tural tourism in terms of revisit the previous place of holidays. Previous studies revealed that tourist preferences are associated with destination attributes, past visits and intention to revisit (Woodside & Lysonski, 1989, Decrop & Snelders, 2005; Li & Hudson, 2016). The attributes that explain the preferences of Europe-ans when intending to revisit the same place of holidays for cultural reasons will be identified. Findings are expected to provide European National Tourism Organ-isations and practitioners an amount of rich insights concerning the identification of return reasons towards cultural tourism preferences.